Engineered Saccharomyces cerevisiae for lignocellulosic valorization: a review and perspectives on bioethanol production - Cunha, Joana Filipa Torres Pinheiro (2020)
The biorefinery concept, consisting in using renewable biomass with economical and energy goals, appeared in response to the ongoing exhaustion of fossil reserves. Bioethanol is the most prominent biofuel and has been considered one of the top chemicals to be obtained from biomass. Saccharomyces cerevisiae, the preferred microorganism for ethanol production, has been the target of extensive genetic modifications to improve the production of this alcohol from renewable biomasses. Additionally, S. cerevisiae strains from harsh industrial environments have been exploited due to their robust traits and improved fermentative capacity. Nevertheless, there is still not an optimized strain capable of turning second generation bioprocesses economically viable. Considering this, and aiming to facilitate and guide the future development of effective S. cerevisiae strains, this work reviews genetic engineering strategies envisioning improvements in 2nd generation bioethanol production, with special focus in process-related traits, xylose consumption, and consolidated bioprocessing. Altogether, the genetic toolbox described proves S. cerevisiae to be a key microorganism for the establishment of a bioeconomy, not only for the production of lignocellulosic bioethanol, but also having potential as a cell factory platform for overall valorization of renewable biomasses.